Energy and Climate : Vision for the Future - McElroy, Michael B. (New York Oxford University Press, 2016)
Introduction -- Energy basics -- The contemporary US energy system : overview including a comparison with China -- Human induced climate change : why you should take it seriously -- Human induced climate change : arguments offered by those who dissent -- Coal : abundant but problematic -- Oil : a volatile past, an uncertain future -- Natural gas : least polluting of the fossil fuels -- Nuclear power : an optimistic beginning, a clouded future -- Power from wind : opportunities and challenges -- Power from the sun : abundant but expensive -- Hydro : power from running water -- Earth heat and lunar gravity : geothermal and tidal energy -- Plant biomass as a substitute for oil in transportation -- Limiting US and Chinese emissions : the Beijing agreement -- Vision for a low carbon energy future.
Include Index
Keywords: Climatic changes -- Energy development -- Power resources